Gambaran tingkat pengetahuan dokter gigi terhadap tata laksana kasus avulsi gigi permanen di wilayah dki jakarta (Laporan Penelitian) - Talsya Happy Forildha; Wiwiek Poedjiastoeti; Bianda Claresta (Fakultas Kedokteran Gigi Universitas Trisakti, 2022)
Background: Avulsion of permanent teeth is one of the most serious dentoalveolar injuries. Appropriate emergency management and a treatment plan are important for a good prognosis. Therefore general dental practitioners (GDPs) must have adequate knowledge regarding the management of permanent avulsed teeth. Objective: Evaluate the knowledge base and preferred methods of general dental practitioners regarding the management of avulsed teeth. Methods: Observativational descriptive with cross-sectional was employed for sample selection. A pre-tested 13-item online questionnaire was distributed to 98 Jakarta GDPs. The data obtained were then categorized into 3 levels which are high (≥76%), moderate (56-75%), and low (≤55%). Results: This study revealed that the majority of GDPs' knowledge is moderate. 21,4% of participants showed good knowledge, while 53,1% are moderate, and the other 24,5% lack the knowledge needed to manage avulsions. Mann-Whitney U test results showed that there was no statistically significant difference between males and females (p = 0.296) nor between the length of practice 0-10 years and >10 years (p = 0.134). Conclusions: The study findings showed that the Jakarta GDPs need to improve their knowledge about the management of permanent avulsed teeth.